Identifying the key beliefs of private university students towards joining the Malaysian Armed Forces - Yong, Wooi Keong *; Maizaitulaidawati, Md. Husin; Liew, Khang Jie *; Sockanathan, Sujitra *; Noraini, Ismail; Muhamad, Radzi Rosly; Othman, Md. Said; Farhana, Syed Ahmad (Inderscience Enterprise Ltd., 2021)
The study investigates Malaysian private university students’ beliefs towards the Malaysian Armed Forces and their enlistment intentions, as a career in the armed forces appears to be an unpopular career choice among non-Malay youths. Primary data via questionnaire will be collected from non-Malay private university students in Malaysia. It is expected that the sample size of 133 respondents will provide insights to the students’ behavioural, normative and control beliefs and this will be able to predict their attitude, subjective norms and perceived behavioural control. The findings agree with previous studies done around the world about youth enlistment in the armed forces. The contribution of this study lies towards identifying the variables that influence non-Malay university student’s intentions to join the Malaysian Armed Forces. The limitations of this study are that it a snap-shot of the recent situation, it is recommended to have a longer-term study.